2005
DOI: 10.1158/1078-0432.ccr-04-1534
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical and Pharmacokinetic Study of Kahalalide F in Patients with Advanced Androgen Refractory Prostate Cancer

Abstract: Purpose: The purpose is to determine the maximum tolerated dose, profile of adverse events, and dose-limiting toxicity of Kahalalide F (KF) in patients with androgen refractory prostate cancer. Furthermore, the pharmacokinetics after KF administration and preliminary antitumor activity were evaluated. KF is a dehydroaminobutyric acidcontaining peptide isolated from the marine herbivorous mollusk, Elysia rufescens.Experimental Design: Adult patients with advanced or metastatic androgen refractory prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 28 publications
1
56
0
2
Order By: Relevance
“…infusion overall agrees with that reported for the other kahalalide F schedule tested to date (12). Both infusion schedules were characterized by linear kinetics for C max and AUC values (at doses up to the recommended dose for phase II studies), a narrow volume of distribution (5.55 liters at the recommended dose with the once-weekly schedule versus 7.16 liters at the recommended dose with the daily schedule), and a short terminal half-life (0.52 h versus 0.47 h, respectively).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…infusion overall agrees with that reported for the other kahalalide F schedule tested to date (12). Both infusion schedules were characterized by linear kinetics for C max and AUC values (at doses up to the recommended dose for phase II studies), a narrow volume of distribution (5.55 liters at the recommended dose with the once-weekly schedule versus 7.16 liters at the recommended dose with the daily schedule), and a short terminal half-life (0.52 h versus 0.47 h, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…infusion. The starting dose (266 Ag/m per week) was chosen after the finding that kahalalide F total doses of up to 1,600 Ag/m 2 given every 3 weeks (in a fractionated daily  5 schedule) were not associated with dose-limiting or drug-related toxicities in a previous phase I study (12). Initially, three patients were treated in each cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that the peptide can be given safely as a onehour i.v. infusion during five days at a dose of 560 µg/m 2 per day once every three weeks [12]. Also in the Phase I clinical stage, another group found that the maximum tolerated dose was 800 µg/m 2 to patients with advanced solid tumors [13].…”
Section: Green Seaweeds As a Source Of New Bioactive Prototypementioning
confidence: 99%
“…Based on these observations, and in view of its acceptable low clinical toxicity profile, elisidepsin has been selected for clinical development (6). In phase I trials Irvalec was shown to be safe, well tolerated and with evidence of activity in patients with solid tumors (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%